Designing new types of integration spaces and Belarusian strategic initiatives - Shcherbin, Vyacheslav K. (Journal of the Belarusian State University. Sociology, 2019)
The article analyses the conceptual content of the concept «space», the widespread use of which in different fields of scientific knowledge is the most obvious indication of «spatial turn», which was outlined in science in the late 1980s. The necessity of designing the new types of integration spaces, the main economic resource of which is the latest scientific knowledge, is justified. Creation of the new types of integration spaces may be a basis of some Belarusian strategic initiatives.